2022
DOI: 10.3389/fonc.2022.988119
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins: New players in breast cancer progression and treatment response

Abstract: Aquaporins (AQPs) are a family of small transmembrane proteins that selectively transport water and other small molecules and ions following an osmotic gradient across cell plasma membranes. This enables them to regulate numerous functions including water homeostasis, fat metabolism, proliferation, migration, and adhesion. Previous structural and functional studies highlight a strong biological relationship between AQP protein expression, localization, and key biological functions in normal and cancer tissues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 185 publications
1
11
0
Order By: Relevance
“…Recent studies suggest [28] that edema may also promote tumor proliferation by inducing abnormal expression of AQP. Aquaporins induce tumor progression and metastasis is a current research hotspot, but part of the mechanism is not clear and needs to be further explored by more clinical and basic research, and relevant targeting drugs are under active trials [29][30]. The integrity of the structure and function of lipid bilayer and membrane proteins in human cell membrane is the physiological basis for the normal PA.…”
Section: Explanation Of the Results Of Analysismentioning
confidence: 99%
“…Recent studies suggest [28] that edema may also promote tumor proliferation by inducing abnormal expression of AQP. Aquaporins induce tumor progression and metastasis is a current research hotspot, but part of the mechanism is not clear and needs to be further explored by more clinical and basic research, and relevant targeting drugs are under active trials [29][30]. The integrity of the structure and function of lipid bilayer and membrane proteins in human cell membrane is the physiological basis for the normal PA.…”
Section: Explanation Of the Results Of Analysismentioning
confidence: 99%
“…While E0771 cells were not responsive to short-term TPM in vivo, AQP4 has been shown to play various roles in breast cancer cells 27,28 , and interventions targeting AQP4 have the potential to impact tumor burden. IHC staining in a cohort of breast cancer BM showed that AQP4 is heterogeneously expressed in BM (percentage positive tumor area ranging from 1.6% to 91.1%, median 10.5%, (Fig.…”
Section: Topiramate Does Not Alter the Response Of Cancer Cells To Ra...mentioning
confidence: 99%
“…Expression of aquaporins in brain tumors and other malignancies has been shown to promote migration and proliferation 38 and can alter the response of conventional anticancer therapies 27,39 ; however, little is known about AQP4 function in BCBM. While AQP4 was expressed in several breast cancer cell lines, the majority were not susceptible to AQP4 blockage (either genetic or via TPM), suggesting that TPM or AQP4 blockage can be used to prevent cytotoxic edema without direct pro or anti-tumoral effects.…”
Section: Disscusionmentioning
confidence: 99%
“…CD19 low B cells highly expressed genes related to cell motility, such as the encoding type III intermediate filament protein (VIM) [51] and S100 calcium-binding proteins (S100A6, S100A13) [52,53], indicating their activation state (Figure 3F). Plasma B cells highly expressed genes related to cell activation (AQP3, GZMA) [54], differentiation (TXNDC5, BHLHA15) [55,56], and antibody production (JCHAIN, MZB1, and HSP90B1) (Figure 3F) [57][58][59][60][61]. GO analysis demonstrated the significant enrichment of genes associated with Golgi vesicle transport, protein folding, endoplasmic reticulum to Golgi vesicle-mediated transport, protein localization to endoplasmic reticulum, and establishment of protein localization to endoplasmic pathways in plasma B cells (Figure 3G).…”
Section: B Cell Response To H5n1-ha Stimulationmentioning
confidence: 99%